4,7-Dimethoxy-6-propyl-2H-1,3-benzodioxole-5-carbaldehyde - Dmitry V. Tsyganov; Victor V. Semenov (Molbank, 2023)
A simple intermediate for the synthesis of methoxy-analogues of coenzymes Q with substituents having various chain lengths based on natural polyalkoxyallylbenzene apiol has been developed.